Single-cell transcriptomics for immune profiling of cerebrospinal fluid in neurological diseases - Ramos-Vicente, David; Monterosso, Paola; de Fàbregues, Oriol; Roch, Gerard; Vila, Miquel; Bové, Jordi (Frontiers in Immunology, 2025)
In this comprehensive review, we delve into the significant body of research on single-cell transcriptomics in cerebrospinal fluid (CSF) to understand neurological diseases with autoimmune, neurodegenerative, infectious, or oncogenic origins. We thoroughly examine all published studies in these areas, with a particular focus on multiple sclerosis, Alzheimer’s disease, and Parkinson’s disease. For these diseases, we review findings related to immune cells that infiltrate the brain, based on postmortem brain tissue analyses and include CSF cytometry findings. Single-cell RNA sequencing (scRNA-seq), single-cell T cell receptor sequencing (scTCR-seq), and single-cell B cell receptor sequencing (scBCR-seq) are increasingly vital tools for studying CSF to understand various aspects of neurological diseases. These advanced techniques allow researchers to explore the etiopathogenesis of these conditions by identifying the roles and interactions of different immune cells. scRNA-seq provides detailed insights into the gene expression profiles of individual cells, revealing how specific cell types contribute to disease progression. scTCR-seq and scBCR-seq enable the study of clonal expansion in T and B cells, respectively, and facilitate antigen prediction, helping to uncover the nature of antigens that trigger adaptive immune responses. By integrating these technologies, scientists can define new therapeutic targets and categorize patients, leading to more personalized and effective treatments. This review highlights the promising advancements and addresses the current limitations of single-cell transcriptomics in the context of CSF and neurological diseases, setting the stage for future breakthroughs.